Modified waste eggshell for the adsorption of FE2+ from aqueous solution - Yeo, Hui Sin (School of Materials Engineering, University Malaysia Perlis, 2016)
In this research, modified waste eggshell was used as adsorbent for Fe (II) removal. Modified and adsorbed eggshell was characterized by Scanning Electron Microscopy (SEM), X-ray Fluorescence (XRF), and Brunauer, Emmet, and Teller (BET), X-ray Diffraction (XRD), Fourier Transform Infrared Spectrum (FTIR). The concentration of ferrous (II) ions was measured by Atomic Adsorption Spectrophotometer (AAS). The performance of ferrous (II) ions removal was studied by different parameters such as pH solution, contact time, initial metal ions concentration and adsorbent dosage with using batch adsorption technique. The result obtained shown the adsorption capacity increased when pH value increased and the optimum pH value was pH 3. The optimum contact time and adsorbent dosage were found out at 10 minutes and 1.0g. The performance adsorption of ferrous ions by modified eggshell was also affected by initial metal ions concentration which had shown the most suitable concentration was 50 ppm.